Determinación de la correlación estadística entre las variables del comportamiento organizacional en la Cooperativa de Producción Agropecuaria Chone LTDA - González Mora, Johana Liceth (2017)
The objective of this research was to determine the statistical correlation between the Organizational Behavior variables with greater incidence for the identification of potential sources of improvement in Cooperativa de Porduccion Agropecuaria Chone Ltda., Located in Chone Canton, the four methodological phases were; determination of variables, evaluation of the variables performance, establishment of the statistical correlation and the action plan. In the first phase, a group of experts were chosen in order they could select the correct variables to be evaluated in the research. In the second phase, the analysis and statistical processing of the obtained information were carried out through the application of the evaluation. In the third, the scatter diagram was used to establish the correlation between the Organizational Behavior variables, and later the details of the causes that were generated by the behavior of these variables were presented. In the fourth phase a plan of action was elaborated based on the results, the goal is to contribute to the improvement of the employees’ organizational behavior. It was concluded that organizational learning is fulfilled at a high level with 79%, in addition the factors with higher scores were teamwork with 89% and organizational structure with 87%, excellent scores, while organizational culture with a high score which is 79%, and the factor with the best score was communication with 85%, and there is a positive correlation between the variables.